Pelanggaran Densus 88 Terkait Tersangka Terorisme Dalam Perspektif Hak Asasi Manusia - Serlyta Indriyanti; Aysya Ratnaningrat (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
Terrorism is a sensitive discussion for Indonesia and internationally. At this time it is important to tackle this crime because it is very dangerous if it is taken lightly. In its efforts to eradicate terrorism, the Indonesian National Police through Densus 88 must have the principle of upholding the law and human rights, as well as not being intolerant. To carry out its duties, Densus 88 must be supervised by an independent institution. Any indication of human rights violations in eradicating terrorism needs to be avoided as much as possible by understanding and evaluating which are regulated in existing regulations, especially regarding the implementation of human rights principles and standards applied in carrying out the duties of the Republic of Indonesia Police. Komnas HAM is of the opinion that shooting to kill terrorist suspects should be avoided except in urgent situations and this must also be shown in a transparent manner and be held accountable according to the law.